Pendidikan Karakter Perspektif Tokoh Lintas Agama: Character Education from the Perspective of Interreligious Leaders - Rif’an Humaidi (Fenomena, 2015)
The discourse on character education has been strongly promoted as an effort to address the aforementioned social issues in education. Therefore, it is no surprise that the discourse on character education is widely discussed, debated, and deliberated across various media, including print (newspapers, magazines, tabloids, bulletins), online platforms, TV, and others. In several academic forums such as seminars, dialogues, discussions, workshops, and training programs, issues related to youth and their disparities are consistently brought up. Even education practitioners engage in addressing these current issues. Wacana mengenai pendidikan karakter begitu kuat diwacanakan. Hal itu sebagai upaya untuk menjawab masalah-masalah sosial pendidikan di atas. Sehingga, tidak heran jika wacana pendidikan karakter begitu ramai diperbincangkan, diperdebatkan, dan didiskusikan mulai dari media cetak (koran, majalah, tabloid, buletin), media online, TV, dan lain sebagainya. Dalam beberapa forum ilmiah, seperti seminar, dialog, sarasehan, workshop, diklat, masalah remaja dan disparitasnya selalu diperbincangkan. Bahkan praktisi pendidikan pun melakukan pendidikan terkait dengan isu-isu aktual tersebut.